What is the Purpose of the Older Brother in the Parable? A Narrative Study of Luke 15 - Blajer, Piotr (2017)
Chapter 15 of Luke is a separate unit within Jesus' journey to Jerusalem (9:51-19:46). It contains three well-known parables, which are often referred to as the "lost" parables or parables of mercy. These three parables are: the Lost Sheep (15:4-7), the Lost Coin (15:8-10) and the Prodigal Son (15:11-32). The three parables in question share a more or less similar pattern (a description of the initial situation, the loss of an asset, the search for it, its discovery and finally the joy that ensues). The only real difference between them is found in the last parable, namely the parable of the Prodigal Son. The older son who faithfully and obediently served his father does not want to partake in the family feast celebrating his brother's return home from a distant country. Thus, he refuses his father's invitation to celebrate the rediscovery of the one that has been lost. The article argues that what at first may seem an unneeded and unnecessary part - the presence of the older brother in the narrative - plays in fact a key role in the whole narrative. The figure of the older brother is crucial to understand the meaning of the parabolic teaching in chap. 15. Consequently, his presence helps to uncover the true identity of the addressees of the parabolic teaching.
Keywords: Bibel; Gleichnis